2013
DOI: 10.4103/0972-0707.108194
|View full text |Cite
|
Sign up to set email alerts
|

Effect of collagen cross-linkers on the shear bond strength of a self-etch adhesive system to deep dentin

Abstract: Objectives:To evaluate the shear bond strength of composite resin to deep dentin, bonded using a self-etch adhesive, after treatment with two collagen cross-linkers at varying time intervals.Materials and Methods:Thirty extracted human incisors were sectioned longitudinally into equal mesial and distal halves (n = 60). The proximal deep dentin was exposed and the specimens were divided based on the surface treatment of dentin prior to bonding as follows: Group I (n = 12, control): No prior dentin surface treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Group III (6.5% GSE) showed significantly higher bond strength to dentin compared with Groups I and IV ( P < 0.001). This is in accordance with the findings of Srinivasulu et al .,[ 3 ] who showed that the application of 6.5% GSE to deep dentin significantly improved the shear bond strength values of composite to dentin compared with the use of 10% sodium ascorbate. The increase in bond strength may be due to the greater number of collagen cross-links which improved collagen stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Group III (6.5% GSE) showed significantly higher bond strength to dentin compared with Groups I and IV ( P < 0.001). This is in accordance with the findings of Srinivasulu et al .,[ 3 ] who showed that the application of 6.5% GSE to deep dentin significantly improved the shear bond strength values of composite to dentin compared with the use of 10% sodium ascorbate. The increase in bond strength may be due to the greater number of collagen cross-links which improved collagen stability.…”
Section: Discussionmentioning
confidence: 99%
“…The major limitations of dentin as a bonding substrate are its heterogeneous composition and hydrophilic nature. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…Naturally occurring collagen cross-linkers such as sodium ascorbate and proanthocyanidin have been reported to increase the collagen cross-linking in the sound and caries-affected dentin ( 9 , 10 ). The positive effect of these collagen cross-linkers on the bond strength of a self-etch adhesive to deep dentin has been reported in the literature ( 7 ). Also, it seems that the efficacy of antioxidant depends on the type of adhesive system ( 11 ).…”
Section: Introductionmentioning
confidence: 80%
“…The durability of the bond between dentin and the adhesive system depends largely on the structural integrity and mechanical properties of acid-demineralized collagen fibers ( 6 ). Covalent inter- and intra-molecular cross-links are the basis for stability, tensile strength and viscoelasticity of collagen fibrils ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of collagen and its resistance to enzymatic degradation can be increased by increasing intra-cross and molecular formation. This can be achieved by using synthetic and natural collagen cross-linker in the dentine substrate before bonding procedures (Vidhya et al, 2013). The use of collagen cross-linking agent is proposed to improve the mechanical prop-erties of the dentine matrix, reduce the level of biodegradation of collagen, increase the nature of dentine resin bonding, and extend the life of adhesive restoration (Castellan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%